2010
DOI: 10.1007/s10940-010-9093-7
|View full text |Cite
|
Sign up to set email alerts
|

Violent Crime, Residential Instability and Mobility: Does the Relationship Differ in Minority Neighborhoods?

Abstract: This study examines the reciprocal relationship between violent crime and residential stability in neighborhoods. We test whether the form of stability matters by comparing two different measures of stability: a traditional index of residential stability and a novel approach focusing specifically on the stability of homeowners. We also examine whether the racial/ethnic composition of the neighborhood in which this stability occurs affects the instability-violent crime relationship. To test the simultaneous rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 55 publications
7
88
0
2
Order By: Relevance
“…In the two high density cities the results were mixed, with a negative relationship in San Francisco but a positive relationship in Honolulu. These results imply that more theoretical consideration needs to be given to how residential stability might impact crime: whereas some research has suggested that it may operate in a multiplicative fashion with other structural neighborhood characteristics hypothesized by social disorganization theory (Warner and Pierce 1993;Warner and Rountree 1997), or that it is dependent on the mix or owners and renters (Boggess and Hipp 2010), the results here suggest that a useful theoretical consideration is how the macro environment might impact this relationship.…”
Section: Discussionmentioning
confidence: 62%
“…In the two high density cities the results were mixed, with a negative relationship in San Francisco but a positive relationship in Honolulu. These results imply that more theoretical consideration needs to be given to how residential stability might impact crime: whereas some research has suggested that it may operate in a multiplicative fashion with other structural neighborhood characteristics hypothesized by social disorganization theory (Warner and Pierce 1993;Warner and Rountree 1997), or that it is dependent on the mix or owners and renters (Boggess and Hipp 2010), the results here suggest that a useful theoretical consideration is how the macro environment might impact this relationship.…”
Section: Discussionmentioning
confidence: 62%
“…Skogan's (1990) disorder and decline model posits that crime has a direct influence on residents' behavior (residents leave the area) and perceptions (residents feel less safe and retreat from social life). As Boggess and Hipp (2010) argue, crime encourages dissatisfaction with the neighborhood which in turn promotes an exodus of those residents with the means to relocate. That crime itself may 8 play a role in how neighborhoods change (Bursik, 1988;Felson 2002;Miethe and Meier 1994;Skogan 1990) suggests the possibility of a reciprocal relationship between crime, the sociostructural characteristics of the neighborhood and the neighborhood processes necessary for regulating unwanted behavior.…”
Section: Poverty Collective Efficacy and Violence: Their Spatial Andmentioning
confidence: 99%
“…9 Residential instability has long been linked to higher crime rates (e.g., Shaw and McKay, 1942) since population fluctuation can impact social networks and the ability of neighborhoods to maintain social control. Instability is also a key factor in the perpetuation of urban disadvantage in Black communities, according to Sampson and Wilson (1995) and Wilson (1987); as households with the financial means leave disadvantaged or high-crime neighborhoods, the community will be less likely to defend itself and fend off negative or undesirable businesses (see also Boggess and Hipp, 2010;Silverman and Segal, 1996). This process can further perpetuate the social isolation that predominantly minority neighborhoods face (Sampson and Wilson, 1995).…”
Section: Control Variablesmentioning
confidence: 99%